The Power to Protect: Household Bargaining and Female Condom Use - Rachel Cassidy; Marije Groot Bruinderink; Wendy Janssens; Karlijn Morsink (Tinbergen Institute, 2020)
Women may face systematically greater benefits than men from adopting certain technologies. Yet women often hold lower bargaining power, meaning that men's preferences may constrain household adoption when decisions are joint. When low female bargaining power constrains adoption of the first-best technology, introducing a version of the technology that is second-best in terms of cost or effectiveness, but more acceptable to men, may increase adoption and welfare. This paper contributes the first explicit model and test of the trade-offs when introducing a second-best technology in such a setting. We conduct a field experiment introducing female condoms (which are less effective and more expensive than male condoms, but often preferred by men) in an area with high HIV prevalence. We observe an increase in the likelihood that women have sex and find strongest adoption of female condoms among women with lower bargaining power, who were previously having unprotected sex.
Keywords: C78; O33; C93; J16; I12; 330